FOREST QUALITY RESEARCH IN MALTA MUNICIPALITY - Šembele, Ina; Teirumnieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
The scientific article contains information about forest stands in the territory of the Malta parish. In the field studies in the plots, the quality of black alder, birch, pine and fir trees has been assessed according to the height, the average, basement area and the number of trees in the plot, and the tree stock is estimated. In general, the quality of forests in the territory of the Malta parish is considered to be good. Problems were detected in the furrows, since after removing the part of valuable materials, the furrows have left branches that are a place of pest control and a potential threat to forest stands. Areas without forest restoration were found.